Formulation and evaluation of darunavir chewable tablets - B. Padmasri; R.Kalyani; K.L. Deepthi; V.Anil kumar; D.Prasanth (International Journal of Pharmacy and Analytical Research, 2016)
In the present work, chewable release tablets of Darunavir were prepared by the wet granulation method. All the tablets were subjected to weight variation, drug content uniformity, and hardness, and friability, dissolution, drug excipients interaction and short-term stability studies. Tablets prepared by the wet granulation method were found to be good without any chipping, capping and sticking. The hardness of the prepared tablets was found to be in the range of 4.2 to 6.4 kg/ cm2. The friability values were found to be in the range of 0.63 to 0.81%. Disintegration time was found to be in the range of 1-3min.Formulation F7 showed good results than rest of the 9 formulations in pre and post compression studies. The average weight and drug content of the prepared tablets indicate weight and drug content uniformity within the batches prepared. Formulation F7 (99.266) displayed maximum drug release within 1 hour and also showed good hardness and friability results. IR-spectroscopic studies indicated that there are no drug– excipients interactions. The optimized formulation follows first order kinetics.